Physical and Biodegradable Characteristics of Palm Wax-Coated Food Packaging Paper: Effect of Propylene Glycol - Muthmainah, Sayyidah; Wulandari, Puji; Najah, Zulfatun; Syabana, Mohamad Ana; Agustina, Siti (Eduvest - Journal of Universal Studies, 2025)
This study aims to evaluate the effect of paper type and concentration of propylene glycol (PG) as plasticizer on the physical characteristics and biodegradability of palm wax coated paper packaging. Tests included thickness, water absorption, oil absorption, tensile strength, and elongation, as well as qualitative biodegradation tests. Palm wax coating imparts hydrophobic properties and increases strength, but its effectiveness is highly dependent on the pore structure and surface morphology of the base paper. PG can optimize homogeneity, flexibility, and interfacial bonding at certain concentrations, but excess PG or interaction mismatches can decrease strength or increase permeability. In particular, samples with A2-type paper showed very low oil absorption, indicating promising potential for food packaging applications that require superior oil barrier properties. In addition, the biodegradation test results showed visual degradation of the samples, confirming the material's ability to biodegrade. This study underscores the importance of specific material combinations to achieve optimal packaging properties. Overall, this palm wax coated paper packaging has the potential to be an eco-friendly food packaging alternative that can help reduce plastic waste.